Karakteristik Limbah Domistik di Kawasan Masyarakat Pesisir: (Studi Kasus di Desa Bajo Indah, Kabupaten Konawe, Provinsi Sulawesi Tenggara) - Ruslan, Ruslan; Rosdiana, Rosdiana; Adami, Aryani (Universitas Muhammadiyah Kendari, 2025)
This research analyzes the characteristics of domestic waste in Bajo Indah Village, Soropia District, Southeast Sulawesi, focusing on the physical, chemical, and biological properties of wastewater from household activities. It aims to raise community awareness about the environmental impacts of pollution due to improper waste management and provide recommendations for more effective practices. Results show that most water quality parameters do not meet the standards set by the Minister of Environment Regulation No. P.68 of 2016, with Total Suspended Solids (TSS) at 68 mg/L (exceeding 30 mg/L), Biochemical Oxygen Demand (BOD) at 25.10 mg/L, Chemical Oxygen Demand (COD) at 80.25 mg/L, and Total Coliform at 4,200 CFU/100 ml (exceeding 3,000 CFU/100 ml). These findings highlight the urgent need for improved wastewater management to mitigate pollution in coastal areas and protect public health and ecosystems.